Comparison of the Gut Microbiota Disturbance in Rat Models of Irritable Bowel Syndrome Induced by Maternal Separation and Multiple Early-Life Adversity - Enqi, Wu; Jingzhu, Song; Lingpeng, Pei; Yaqin, Ling (Frontiers in Cellular and Infection Microbiology, 2021)
Background: The study aimed to identify the effect of modeling procedures on bacterial communities and to investigate whether different modeling procedures lead to consistent patterns of gut microbiota compositions. Methods: Two IBS rat models (MS alone and multiple-early-adversity modeling) were established and the gut microbiotas were analyzed using 16S-rRNA-based high-throughput sequencing methods. Results: Rats from both models exhibited visceral hypersensitivity and the two model groups exhibited differences in the extent of visceral sensitivity and fecal water content. The microbial community structure of the two models exhibited significant differences compared to the controls, while the two model groups also exhibited significant differences between them. Furthermore, microbial community functional predictions suggested that the two models exhibited different abundances of metabolisms and pathways. Several common and distinct characteristic differences were also observed between the two model groups. Alloprevotella were more abundant in both model groups, while Butyricicoccus, Turicibacter, Ruminococcus, and Clostridium_sensu_stricto along with the family it belongs to were less abundant relative to controls. In addition, the abundance of Clostridium_IV, Corynebacterium, Rothia, Elusimicrobium, Romboutsia, Allobaculum, Parasutterella and their related taxa were specifically associated with MS group, whereas Butyricimonas and Vampirovibrio along with its related taxa were specifically associated with MAM group. Among those, Butyricimonas, Butyricicoccus and Corynebacterium were found partially mediates early adversity exposure-induced visceral hypersensitivity. Conclusions: our results highlight the importance in evaluating gut microbiota characteristics in IBS research while also systematically considering potential modeling procedural differences. The microbial compositional/functional differences identified in this study were suggestive to further investigation of mechanism of early adversity induced IBS.